Web Informasi Geografis untuk Spasial Sawah dan Identifikasi Kesuburan Tanah Menggunakan Metode RAD - Taufiq, M.; Chusyairi, Ahmad (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2019)
Banyuwangi is one of the districts in East Java Province which is on the eastern tip of Java Island where the population has a livelihood as a farmer. Agriculture is one of the priority sectors of regional development in Banyuwangi Regency. One effort was made to support the Department of Agriculture in mapping rice fields for organic and inorganic agriculture in Banyuwangi Regency by using a web-based Geographic Information System that can produce information about spatial fields and identification of soil fertility from the results of testing in soil laboratories. The method used in this study is Rapid Application Development (RAD). The conclusion obtained in this study is the Web Geographical Information can inform the spatial fields and identify soil fertility using the RAD method, so that it can support the Agricultural Service in mapping rice fields in Banyuwangi Regency.Keywords — Banyuwangi, Department of Agriculture, RAD, Web Geographic Information